TINJAUAN YURIDIS PELAKSANAAN PEMBEBANAN FIDUSIA DENGAN SURAT KUASA JAMINAN FIDUSIA DIBAWAH TANGAN MENURUT UU No. 42 TAHUN 1999 DI PT BPR ARTHA TANAH MAS SEMARANG - Nadia Febiana Yusuf; Arikha Saputra (LPPM STIH Awang Long, 2023)
The process of creating a fiduciary guarantee is carried out through the imposition stage which is carried out before a notary and the fiduciary guarantee registration stage. In practice, currently there is widespread use of power of attorney to charge fiduciaries under the hand to make fiduciary deeds before a notary. The problem in this study is how the process of implementing fiduciary imposition with a private power of attorney for fiduciary guarantees according to Law no. 42 of 1999 at PT BPR Artha Tanah Mas Semarang and how is the legal force of the fiduciary deed made through a power of attorney under the fiduciary guarantee. The approach method is empirical juridical, descriptive analytical research specifications, data sources are primary data and secondary data. Data collection methods are field studies and literature studies, data analysis is qualitative. The results of the study show that the process of implementing fiduciary imposition with a power of attorney for fiduciary guarantees is underhand according to Law no. 42 of 1999 at PT BPR Artha Tanah Mas Semarang, the debtor signs a power of attorney for fiduciary guarantees, then the bank faces itself before the notary to make a fiduciary guarantee deed for further registration at the Fiduciary Registration Office. The fiduciary deed made through a power of attorney under the hand of fiduciary guarantees is basically valid, but if there is a lawsuit or intervention from another party, the power of attorney under the hand of fiduciary has weaknesses in the verification process, where the position of the power of attorney under the hand is very weak and lacks legal certainty.